HIGH LATEX YIELDING AND DISEASE RESISTANCE OF RUBBER CLONES IRR 200 SERIES - Aidi- Daslin; Sekar Woelan; Syarifah Aini Pasaribu (Indonesian Agency for Agricultural Research and Development, 2012)
Rubber clones of Indonesian Rubber Research (IRR) 200 series have been produced from intensive breeding program started in 1985. Some clones showed superior characteristics such as high latex yielding, vigorous, and disease resistant. This study aimed to test their performances in a field trial conducted since 1999 at Sungei Putih Experimental Garden, North Sumatra. The experiment was designed in a randomized block, using twelve IRR clones as treatment and PB 260 clone as control, three replications. Planting distance was 5 m x 4 m and plot size was 10 rows x 50 trees. Observations were made on girth size of the 2, 3 and 4 year-old trees, dry rubber yield following the 1/2S d/2 and 1/2S d/3.ET2.5% tapping systems, bark thickness, rings number and diameter of latex vessels, as well as leaf fall diseases intensities of 3-5 year-old trees. The results showed four IRR 200 clones, i.e. IRR 207, IRR 208, IRR 211 and IRR 220 produced high latex. Using the 1/2S d/2 tapping system, three clones with highest dry rubber yield were obtained, namely IRR 208 (49.8 g tree-1 tapping-1 or g t-1 t-1), IRR 211 (48.8 g t-1 t-1) and IRR 220 (52.0 g t-1 t-1), whereas that using the 1/2S d/3. ET2.5% tapping system, their yields were 63.2 g, 64.3 g, and 66.2 g t-1 t-1, respectively. At four year-old, these clones had girth size of 41.4-51.0 cm, girth increment 9.7-11.6 cm year-1, bark thickness 6.3-7.2 mm, latex vessel rings number 6.8-7.0, and diameter of latex vessels 23.75-26.57 mm. All of the clones were moderately resistant to Colletotrichum, Oidium and Corynespora leaf fall diseases. This study suggests that IRR 207, IRR 208, IRR 211 and IRR 220 rubber clones are suitable for commercial stake holders and the recommended tapping system is 1/2S d/3.ET2.5%.Bahasa IndonesiaKaret klon IRR (Indonesian Rubber Research) seri 200 dihasilkan melalui program pemuliaan yang intensif mulai tahun 1985. Beberapa klon menunjukkan karakteristik unggul sebagai penghasil lateks tinggi, jagur, dan tahan terhadap penyakit. Penelitian ini bertujuan untuk menguji kinerja klon pada percobaan lapangan yang dibangun tahun 1999 di Kebun Percobaan Sungei Putih, Sumatera Utara. Percobaan dirancang dalam acak kelompok dengan perlakuan dua belas klon IRR dan kontrol klon PB 260, tiga ulangan. Jarak tanam 5 m x 4 m dan luas plot 10 baris x 50 pohon. Pengamatan dilakukan terhadap ukuran lilit batang pada umur 2, 3 dan, 4 tahun, hasil karet kering dengan sistem sadap 1/2S d/2 dan 1/2S d/3.ET2,5%, tebal kulit, jumlah cincin, dan diameter pembuluh lateks. Intensitas serangan penyakit gugur daun diamati pada tanaman berumur 3 dan 5 tahun. Hasil penelitian menunjukkan empat klon karet IRR seri 200 yaitu IRR 207, IRR 208, IRR 211, dan IRR 220 menghasilkan lateks yang tinggi. Dengan sistem sadap 1/2S d/2, tiga klon memiliki hasil karet kering paling tinggi, yaitu IRR 208 (49,8 g pohon-1 sadap-1 atau g p-1 s-1), IRR 211 (48,8 g p-1 s-1), dan IRR 220 (52,0 g p-1 s-1), sedangkan menggunakan sistem sadap 1/2S d/3. ET2,5%, hasil masing-masing klon adalah 63,2 g, 64,3 g, dan 66,2 g p-1 s-1. Pada umur empat tahun, klon-klon ini memiliki ukuran lilit batang 41,4-51,0 cm, pertambahan lilit batang 9,7-11,6 cm tahun-1, ketebalan kulit 6,3-7,2 mm, jumlah cincin pembuluh lateks 6,8-7,0, dan diameter pembuluh lateks 23,75-26,57 mm. Semua klon tahan terhadap penyakit gugur daun Colletotrichum, Oidium, dan Corynespora. Dengan demikian, klon karet IRR 207, IRR 208, IRR 211, dan IRR 220 cocok dikembangkan secara komersial dan sistem sadap yang dianjurkan adalah ½S d/3.ET2,5%.